Evaluating the performance of different thermal indices on quantifying outdoor thermal sensation in humid subtropical residential areas of China - Li, Kunming; Liu, Xiao; Bao, Ying (Frontiers in Environmental Science, 2022)
Considerations of urban microclimate and thermal comfort are necessary for urban development, and a set of guidelines for a comfortable microclimate must be developed. However, to develop such guidelines, the predictive ability of thermal indices for outdoor thermal perceptions under different design decisions must be defined. The present study aimed to determine suitable indices for assessing outdoor thermal reaction in humid subtropical residential areas of China. Five criteria of coefficients of determination, Spearman’s rho, percentage of correct prediction, percentage of thermal comfort indices’ class predictions, and distribution of thermal comfort indices’ class predictions per class of thermal sensation votes (TSV) were established to assess the performance of four thermal indices commonly used in outdoor thermal comfort research of China. The empirical thermal comfort index (TSVmodel) had a better correlation with TSV, while the Universal Thermal Climate Index (UTCI) was the most successful, simulating 29.8% of TSV. The testability of Physiologically Equivalent Temperature (PET) and Standard Effective Temperature (SET*) were very low, with the correct predictive ability 16.5% and 24.4% respectively. In the selected indices, the UTCI reasonably approximated the observed data for this study and was recommended to assess the outdoor thermal comfort for evaluating the thermal comfort level under different design decisions. For all the indices, the systematic errors were generally higher than the unsystematic errors, indicating that the assessment scales do not adapt to humid subtropical residential areas of China. It is necessary to establish the thermal sensation ranges of humid subtropical areas of China.